VARIED ROLES OF METAPHORIC EXPRESSIONS IN PEPALI BABAD BANYUMASAN - Rahayu Pristiwati; Dyah Prabaningrum (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to examine the various roles of metaphor in the oral literature of Pepali Babad Banyumasan. This study was qualitative and descriptive by its nature, meaning that all data are not in the form of numbers. It instead focused on the quality of verbal forms or utterances All data were retrieved from written excerpts of the prose. All data were retrieved from written excerpts of the prose. These data were further analyzed using a referential identity method and a reflective introspective method. The study found four functions of metaphor in Pepali Babad Banyumasan, such as to mention unique characteristics, to describe the place of origin, to substitute, and to concretize human experience. Oral literature of Banyumasan Javanese, especially the one discussed in the present study, is worth investigating. Pepaliis originated from Raden Baribin, Wira Utama, Yudanegara II, Yudanegara III, and others. Behind the fact that literary work is something inanimate, lies within Pepali is enigma and meaning to look at. The findings in this study are belief in magical and occult things as a way of life for taking attitudes for the ancient Javanese people, particularly the Banyumasan people that was used as a form of expression to concretize the representation of experiences in the past, then make it a message so that people are more vigilant and break bad luck in the present by reflecting on past experiences. In this study, it is clear that the ancient Javanese people believed in magical things as a form of human communication to get blessing in managing government. The ancient Javanese people of Banyumasan also believed that the name was also a sign to represent the image of the community group. In this case the name that appears to represent the aristocratic class of society (people who are destined to become leaders) by giving him a family name taken from the name of an animal, namely goose.